Analisis Sistem Audit Keuangan Sektor Publik Beserta Standar dan Regulasi yang Berlaku - Zein, Alfina Zahra; Batubara, Efrida Handayani (CV. Pusdikra Mitra Jaya, 2025)
Public sector audits are a crucial element in ensuring accountability and transparency in state financial management. As public demand for good governance increases, the role of public sector audits is increasingly under scrutiny. Public sector audits aim to evaluate whether the use of state financial resources has been carried out economically, efficiently, and effectively, and in compliance with regulations. This type of research is qualitative research, which means collecting data naturally with the aim of interpreting the phenomena that occur where the researcher is a key instrument. The characteristics of qualitative research are: 1) conducted in natural conditions, 2) more descriptive, 3) paying attention to processes as well as products, 4) tending to analyze data inductively. The history of public sector audits in Indonesia began in the reform era with demands for better state financial management, free from corruption, collusion, and nepotism, and accountability. Public sector audits have experienced ups and downs, but continue to develop with the enactment of laws in the field of state finance. The main differences between public sector audits and business sector audits lie in motivation, funding sources, accountability, organizational structure, accounting systems, financial reports, accounting standards, auditors involved, and audit standards used. The public sector financial audit cycle consists of several stages, namely audit planning, establishing regulations, preparing audit programs, conducting audits, making lists of findings, discussing audit results, completing reports, following up on findings, and issuing audit report results. The techniques used in public sector financial audits include analytical procedures, inspections, confirmations, inquiries, calculations, tracing, examining supporting evidence, observations, re-execution, computer-assisted audit techniques, tests of controls, and substantive tests.